2017
DOI: 10.1038/ng.3919
|View full text |Cite
|
Sign up to set email alerts
|

A gene encoding maize caffeoyl-CoA O-methyltransferase confers quantitative resistance to multiple pathogens

Abstract: Alleles that confer multiple disease resistance (MDR) are valuable in crop improvement, although the molecular mechanisms underlying their functions remain largely unknown. A quantitative trait locus, qMdr, associated with resistance to three important foliar maize diseases-southern leaf blight, gray leaf spot and northern leaf blight-has been identified on maize chromosome 9. Through fine-mapping, association analysis, expression analysis, insertional mutagenesis and transgenic validation, we demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
138
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(157 citation statements)
references
References 85 publications
3
138
0
Order By: Relevance
“…The gene Caffeoyl‐CoA O‐methyltransferase 2 ( ZmCCoAOMT2 ) is a key functional gene in the lignin metabolic pathway and upregulated (> five‐fold) when ZmWAK‐RLK1 is present before pathogen inoculation. Recently, this gene was shown to be associated with resistance against multiple foliage diseases including NCLB (Yang et al ., ), suggesting a link between ZmWAK‐RLK1 , lignin and NCLB resistance. Because c .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The gene Caffeoyl‐CoA O‐methyltransferase 2 ( ZmCCoAOMT2 ) is a key functional gene in the lignin metabolic pathway and upregulated (> five‐fold) when ZmWAK‐RLK1 is present before pathogen inoculation. Recently, this gene was shown to be associated with resistance against multiple foliage diseases including NCLB (Yang et al ., ), suggesting a link between ZmWAK‐RLK1 , lignin and NCLB resistance. Because c .…”
Section: Discussionmentioning
confidence: 96%
“…The gene Caffeoyl-CoA O-methyltransferase 2 (ZmCCoAOMT2) is a key functional gene in the lignin metabolic pathway and upregulated (> five-fold) when ZmWAK-RLK1 is present before pathogen inoculation. Recently, this gene was shown to be associated with resistance against multiple foliage diseases including NCLB (Yang et al, 2017a), suggesting a link between ZmWAK-RLK1, lignin and NCLB resistance. Because c. 50% of DEGs showed differential expression even before pathogen infection, this suggests a constitutive ZmWAK-RLK1-mediated immune response that might be expressed independently of the recognition of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized metabolic pathways that give rise to diverse arsenals of bioactive defense compounds allow plants to fend off pathogen attacks. The significance of plant specialized metabolism in agriculture is exemplified by the association of specific biosynthetic genes with resistance against insect pests and phytopathogens (Meihls et al, 2013;Handrick et al, 2016;Yang et al, 2017). Such studies highlight the potential of enlisting naturally occurring specialized metabolites in crop species to enhance quantitative disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, SLB QTL identified in bin 9.03/9.02 have been identified in three previous studies using population derived from different crosses (Belcher et al, ; Negeri et al, ; Zwonitzer et al, ). Yang et al () identified qMdr 9.02 localized on maize chromosome 9, associated with resistance to three important foliar maize diseases: SLB, gray leaf spot and northern leaf blight. The unique SLB resistance‐related QTL in bins 1.06, 4.01, 6.01 and 9.02 were detected by Li et al () in the environments of the United States and China.…”
Section: Discussionmentioning
confidence: 99%